Basic researchVariation in serum level of IL-2 and IL-8 in lung fibrosis - Ezzeldin, Nada; Saad, Nevine E.; Ezzeldin, Howayda; Mohsen, Mona (Archives of Medical Science, 2008)
Introduction: An imbalance between the Th1 and Th2 cytokines indicates the development of the fibrotic response. This study focus on the mediators that influence the imbalance in pulmonary fibrosis by assessing the variation in the serum level of IL-2 (type-1 cytokine) and IL-8 (type-2 cytokine). Material and methods: This study included 25 patients with lung fibrosis and ten healthy children as a control group. The lung fibrosis group was subdivided into diffuse and localized according to the pattern of fibrosis. Causes of diffuse lung fibrosis were SLE or post chemotherapy course due to malignancies; those of localized fibrosis were unresolved pneumonia or old pulmonary tuberculosis. There was a significant increase in serum level of IL-8 and an insignificant increase in serum level of IL-2 in pulmonary fibrosis group compared with the control (p=0.02, p=0.06) respectively. Results: There was a significant increase in the serum level of IL-2 in diffuse lung fibrosis group compared with that of control (p=0.004) and localized lung fibrosis (p=0.01) groups. There was no increase in the serum level of IL-8 in diffuse lung fibrosis group compared with that of control group (p=0.9). The localized lung fibrosis group shown significant increase in the serum level of IL-8 compared with the control (p=0.002) and the diffuse lung fibrosis groups (p=0.02) respectively. Conclusions: In conclusion, the imbalance between IL-8 (Th2) and IL-2 (Th1) cytokines in pulmonary fibrosis with the predominance of Th2, as compared to Th1 cytokines is important in progression of fibrosis.